2016
DOI: 10.3732/apps.1500091
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of polymorphic microRNA‐based microsatellite markers in Nelumbo nucifera (Nelumbonaceae)

Abstract: Premise of the study:Polymorphic microRNA (miRNA)–based microsatellite markers were developed to investigate the genetic diversity and population structure of Nelumbo nucifera (Nelumbonaceae).Methods and Results:A total of 485 miRNA-based microsatellites were found from the genomic DNA sequences of N. nucifera. After several rounds of screening, 21 primer pairs flanking di-, tri-, or pentanucleotide repeats were identified that revealed high levels of genetic diversity in four populations with two to five alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, the consequences of the same in non-coding transcripts are less studied. A very few reports demonstrated the significance of analysis of SSRs in non-coding miRNA [ 12 15 , 49 ]. In current study, 13 of 33 total predicted pre-miRNAs had one or more SSR motifs (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the consequences of the same in non-coding transcripts are less studied. A very few reports demonstrated the significance of analysis of SSRs in non-coding miRNA [ 12 15 , 49 ]. In current study, 13 of 33 total predicted pre-miRNAs had one or more SSR motifs (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Predominant of such markers like SSR, ISSR, EST-SSR have been effectively utilized in several crop improvement program [ 7 – 11 ]. MicroRNA precursor based SSR markers are very recently incorporated in this chapter and mostly utilized in marker trait association analysis in several species [ 12 15 ]. These micro RNAs are short, non-coding RNA molecules, involved in post transcriptional mode of gene regulation and [ 16 ] thus effects on related phenotype [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Bonferroni correction method, which estimates a threshold p-value to control the false positive rate, is based on the assumption that every genetic variant tested is independent of the rest (Kaler and Purcell, 2019). However, this is also considered as the most conservative method and many important loci may not qualify the stringent criterion of significance test (Wang et al, 2016). Hence, each of the markers identified can be utilized later on, for a larger population (especially from a mapping population) to check their true associations and heritability.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the same authors reported identification of 129 miR‐SSRs in conserved miRNA genes; 20 of these SSRs, each had seven or more repeats (Ganie & Mondal, ). In M. truncatula, a total of 169 primer pairs were successfully designed from 130 miRNA genes (Min et al, ); (b) in lotus ( Nelumbo nucifera ), 1,000 bp sequences (500 bp flanking 5′ and 3′ ends) each in 106 pre‐miRNAs were screened for the presence of miR‐SSRs using MISA; 45 miR‐SSRs were identified in 36 genotypes (Wang, Gui, Pan, Hu, & Ding, ). (c) In tea ( Camellia sinensis ), using an online program WebSat, 18 SSRs were identified in 13 of 33 predicted miRNAs that were located in ESTs; primer pairs flanking each SSR were designed with the help of BatchPrimer3 server (Hazra, Dasgupta, Sengupta, & Das, ).…”
Section: Polymorphisms Involving Mirnas and Target Sitesmentioning
confidence: 99%